Aircraft carrier or ballistic missile defense: Signaling commitment in situations of uncertainty. Issue 5 (19th October 2016) - Handberg, Roger
ABSTRACT: Strategically, the United States is in a period characterized by uncertainty and diverse threats. Attempting to end two wars becomes background noise in the larger context of U.S. recalibration of its role in the world. U.S. power is perceived as either declining or being reoriented. Balancing off previous commitments with new ones becomes a critical and difficult task. The core problem becomes signaling commitment without deploying major forces to a particular location. Aircraft carriers are important symbolic instruments signaling U.S. interest regarding a particular issue. Those vessels are the linear descendants of battleships formerly the symbol of British power. Such deployments, however, are limited by being a ship, especially in disputes distant from the sea. Ballistic missile defense has come to occupy that role in signaling American commitment to allies or a state threatened by another. This can come as part of an alliance such as NATO's commitment of Patriot PAC-3 units to Turkey, with units drawn from three separate militaries including the United States.